Staatsorganisationsrecht Klausur- und Examenswissen - Chiofalo, Valentina; Linke, Louisa; Kohal, Jaschar R. A. (De Gruyter Studium, 2022)
This textbook, written by university researchers, contains basic knowledge about German state organization law (Staatsorganisationsrecht). It presents exam-relevant material specifically for students. It also contains in-depth excurses on specific topics, provided they deepen understanding. With numerous example formulations and interactive exercises, it also helps students to acquire case-solving techniques for state organization law.